Computational study of linear carbon chain based organic dyes for dye sensitized solar cells. Issue 2 (4th January 2023) - Consiglio, Giuseppe; Gorcyński, Adam; Petralia, Salvatore; Forte, Giuseppe
Abstract : Photophysical properties of a new family of LCC-based dyes for applications in DSSC are predicted. Superior properties are shown by compounds with pyrrole ring as donor group, PY-3N is expected to be a promising candidate for applications. Abstract : Spectroscopic, electronic and electron injection properties of a new class of linear carbon chain (LCC) based organic dyes have been investigated, by means of density functional theory (DFT) and time-dependent density functional theory (TDDFT), for application in dye-sensitized solar cells (DSSCs). The photophysical properties of LCC-based dyes are tuned by changing the length of the linear carbon chain; UV/VIS absorption is red-shifted with increasing LCC length whereas oscillator strength and electron injection properties are reduced. Excellent nonlinear optical properties are predicted in particular for PY-N4 and PY-S4 dyes in the planar conformation. Results indicate that a LCC-bridge produces better results compared to benzene and thiophene bridges. Simulations of I − -Dye@(TiO2 )14 and Dye@(TiO2 )14 anatase complexes indicate that designed dyes inject electrons efficiently into the TiO2 surface and can be regenerated by electron transfer from the electrolyte. Superior properties in terms of efficiency are shown by compounds with a pyrrole ring as the donor group and PY-3N is expected to be a promising candidate for applications, however all the investigated dyes could provide a good performance in solar energy conversion. Our study demonstrates that computational design can provide a significant contribution to experimental work; we expect this study will contribute to future developments to identify new and highly efficient sensitizers.